Influence of ethnicity on response to asthma drugs. (July 2015) - Cazzola, Mario; Rogliani, Paola; Sanduzzi, Alessandro; Matera, Maria Gabriella
<x xml:space="preserve">Abstract</x> Introduction: Understanding variability in the response to asthma medications is essential to ensure appropriate prescribing. Given that there are increased asthma treatment failures observed in ethnic minorities receiving asthma therapeutics, it is fundamental to understand the factors related to ethnicity that can modify the response to asthma therapy. Areas covered: Race/ethnicity is an important determinant of drug response and therefore contributes to interindividual variability. It is generally recognized that its effects on drug response are determined by both genetic and environmental factors to a varying extent, depending on the ethnic groups and probe drugs studied. Also, adherence to therapy can influence pharmacological response to asthma therapeutics. Expert opinion: Health-care professionals might never use the treatment in their patients irrespective of their ethnicity and thus inadvertently increase ethnic health inequality. However, our understanding of whether and/or how ethnicity influences pharmacological response to asthma therapeutics is still very scarce. A holistic, integrative systems biology approach that combines large-scale molecular profiling traits (e.g., transcriptomic, proteomic, metabolomic traits) and genetic variants could help to personalize the treatment of asthmatic patients regardless of race/ethnicity.